Analisis Kemampuan Peserta Didik dalam Aspek Pengetahuan Sikap Keterampilan pada Pembelajaran Tematik Secara Daring - Hanim Muchotun; Asep Ardiyanto; Diana Endah Handayani (STKIP Andi Matappa Pangkep, 2022)
The current increase in the danger status of COVID-19 requires that there is a restriction (lockdown) on the spread of COVID-19 which is getting bigger by the day,making face-to-face teaching and learning activities change by implementing Work From Home (WFH) using an online learning system for a longer period of time.The concept of the 2013 curriculum is expected to provide a balance of competency characteristics from the knowledge aspect,attitude aspect,and skills aspect that can balance these three aspects.There is a decrease in performance in every aspect.The approach used in this study is a qualitative approach.The stage of achievement in the ability aspect of knowledge from C1,C2,C3 to C4.The stage of achievement on the ability aspect of the attitude from A1,A2, to A3.The stage of achievement in the ability aspect of skills from P3 to P4.